Penghijauan di Kelurahan Babakan Surabaya - Endang Amalia; Ucu Nugraha; Dani Hamdani (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
This Community Service is the implementation of Greening Activities in Protecting the Environment at Kelurahan Babakan Surabaya Kiaracondong Bandung office held on June 21, 2023. The activity carried out in this Community Service is in the form of distributing 20 pots with a diameter of 50 cm. The target of this community service activity is the preservation of reforestation of community areas and vacant land to restore its function of holding and storing water. So that it looks green and not arid. The existence of trees that hold and store water makes springs function.